New Report of Costalimaita ferruginea Fabricius (Coleoptera: Chrysomelidae) on Eucalyptus sp. (Myrtaceae) in Sinop - Mato Grosso, Brazil - Pires, Evaldo Martins; Corassa, Janaína de Nadai; Barreto, Marliton Rocha; Soares, Marcus Alvarenga (EntomoBrasilis, 2013)
Costalimaita ferruginea (Fabricius) (Coleoptera: Chrysomelidae) is the main Coleoptera defoliator of eucalyptus in Brazil and has a strong association with plants of the family Myrtaceae, bein the eucalyptus important for the sectors of energy, paper, pulp and furniture industry. The objective of the present study was to record the occurrence of this Chrysomelidae in eucalyptus plants in Sinop, State of Mato Grosso, Brazil, during the months of November 2010 to January 2011, thus contributing to increase in knowledge on the geographic distribution of this insect and also hypothesize that the Coleoptera may soon become a major pest of eucalyptus in the state of Mato Grosso. Novo Registro de Costalimaita ferruginea (Fabricius) (Coleoptera: Chrysomelidae) em plantas de Eucalyptus sp. (Myrtaceae) em Sinop - Mato Grosso, Brasil Resumo. Costalimaita ferruginea (Fabricius) (Coleoptera: Chrysomelidae) é o principal Coleoptera desfolhador de eucalipto do Brasil e possui grande associação com plantas da família Myrtaceae, sendo o eucalipto importante nos setores de energia, papel, celulose e indústria moveleira. O objetivo deste estudo foi registrar a ocorrência desse Chrysomelidae em plantas de eucalipto município de Sinop, Mato Grosso, Brasil, durante os meses de novembro de 2010 a janeiro de 2011, contribuindo assim para o aumento no conhecimento sobre a distribuição geográfica desse inseto e ainda, lançar a hipótese de que brevemente esse Coleoptera poderá ser tornar uma importante praga da eucaliptocultura do estado de Mato Grosso.